Extraction of sulfated agar from Gracilaria lemaneiformis using hydrogen peroxide-assisted enzymatic method. (15th March 2020) - Chen, Huijing; Xiao, Qiong; Weng, Huifen; Zhang, Yonghui; Yang, Qiuming; Xiao, Anfeng
Graphical abstract: Highlights: High sulfate and low viscosity agar was extracted by H2 O2 -assisted enzymatic method. The filtration and dehydration rates of agar were improved after H2 O2 treatment. The agar exhibited high sulfate content was revealed by ESI-TOF-MS. Abstract: In this study, an eco-friendly extraction method was explored to obtain high sulfate content agar and repair the deficiency of enzymatic extraction by taking full advantage of H2 O2 . The sulfate content of EHA (H2 O2 -assisted enzymatic extracted agar) reached 3.56 %, which is significantly higher than that of traditional alkali-extracted agar (AA, 1.8 %). Moreover, EHA exhibited lower viscosity (9.4 cP), which improved 26.6 % and 14 % of filtration and gel dehydration rates than EA (enzymatic extracted agar), respectively. Additionally, the physicochemical properties of the agars were evaluated and compared. Among these agars, EHA showed some favorable properties, such as high yield (16.08 %) and low dissolution temperature (88.9 °C). The surface of algae became smoother after treatment with H2 O2 due to effective degradation of cellulose. Besides, mass spectrometry analysis revealed that EHA preserved a great amount of sulfate, while thermogravimetric analysis suggested that the thermal stability of EA and EHA both decreased.